Trade cooperation between China and Pakistan: Geo-Strategic and Geo-Political Perspective (Journal of Politics and International Studies, 2025)
The economic ties between China and Pakistan have deep historical roots, dating back to the 1950s. This relationship holds immense significance for both countries, as well as for broader geoeconomic and geopolitical landscape of the region. Over the decades, it has evolved from primarily political and strategic alignment to encompass robust economic cooperation as well. China has emerged as the largest trading partner of Pakistan, with bilateral trade reaching over $60 to 65 billion in 2024. Despite the changes in geostrategic and geopolitical environment of South Asia, relations between China and Pakistan have remained strong and stable. This research paper aims to analyze role and impact of geopolitical and geoeconomic position of South Asian region in determining the trade relations between Pakistan and China. Inferences are made by using qualitative approach and secondary data. This research has also provided a comprehensive analysis of the historical context, theoretical underpinnings, and the key trade and investment agreements that have shaped the China-Pakistan economic relationship in South Asian region. This research concludes that this unique relation and partnership is going to boost Pakistan’s exports, reduce costs of doing business, and will integrate it into regional and global supply chains. The trade and economic cooperation between the two countries has evolved into a crucial component of their broader strategic partnership, with significant implications for the regional political, strategic and economic landscape.